2005
DOI: 10.1093/toxsci/kfi325
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Induction of Aromatase (CYP19) Activity by Brominated Flame Retardants in H295R Human Adrenocortical Carcinoma Cells

Abstract: Brominated flame retardants (BFRs) are persistent and ubiquitous chemicals in the environment, and they are found at increasing levels in tissues of wildlife and humans. Previous in vitro studies with the BFR class of polybrominated diphenyl ethers (BDEs) have shown endocrine-disrupting properties. Our study assessed the potential effects of nineteen BDEs, five hydroxylated BDEs (OH-BDEs), one methoxylated BDE (CH(3)O-BDE), tetrabromobisphenol-A (TBBPA), its dibromopropane ether derivative (TBBPA-DBPE), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 37 publications
4
67
1
Order By: Relevance
“…Previous studies on the effects of this chemical revealed that TBP causes developmental neurotoxicity, embryotoxicity, and fetotoxicity in rats (Lyubimov et al, 1998). In addition, it is a potent competitor of the thyroid hormone (thyroxine, T4), which was indicated by the results of the in vitro TTR-binding assay (Legler and Brouwer, 2003;Hamers et al 2006;Suzuki et al, 2008); it showed weak estrogen-like activity in the human breast cancer cellline MCF-7 (Olsen et al, 2002); TBP caused an induction of aromatase activity in human adrenocortical (H295R) cell line (Cantón et al, 2005), and it induces neuroblastoma cell differentiation (Ríos et al, 2003) and disturbs cellular Ca 2+ signaling in neuroendocrine cells (PC12) (Hassenklöver et al, 2006). Exposure to TBP has also been shown to affect the development of zebrafish embryos .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effects of this chemical revealed that TBP causes developmental neurotoxicity, embryotoxicity, and fetotoxicity in rats (Lyubimov et al, 1998). In addition, it is a potent competitor of the thyroid hormone (thyroxine, T4), which was indicated by the results of the in vitro TTR-binding assay (Legler and Brouwer, 2003;Hamers et al 2006;Suzuki et al, 2008); it showed weak estrogen-like activity in the human breast cancer cellline MCF-7 (Olsen et al, 2002); TBP caused an induction of aromatase activity in human adrenocortical (H295R) cell line (Cantón et al, 2005), and it induces neuroblastoma cell differentiation (Ríos et al, 2003) and disturbs cellular Ca 2+ signaling in neuroendocrine cells (PC12) (Hassenklöver et al, 2006). Exposure to TBP has also been shown to affect the development of zebrafish embryos .…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of 2,4,6-TBP for calcium signals (reduction of calcium entry and release from intracellular stores) indicates the toxicity of this substance and therefore its impact on developmental processes, since calcium signals are crucial for hormonal and therefore developmental regulation. In addition, 2,4,6-TBP induces aromatase activity, which balances estrogen levels (Cantón et al, 2005). 2,4-DBP comparably reduces in-and outward currents; this interesting finding suggests more general target structures and target molecules for this compound and in support of this, 2,4-DBP binds to estrogen receptors as possible endocrine disruptors (Olsen et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…Reduction of CYP19 gene expression might result in a loss of aromatase enzyme concentrations and activities. It has been hypothesized that the alteration of aromatase activity by various chemicals represents a potential mechanism of endocrine disruption (Cantón et al 2005;Sanderson et al 2000Sanderson et al , 2004. It is possible that TBC might exert anti-estrogenic effects via aromatase inhibition if this mechanism could occur in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 99%